Mechanisms of Rice Endophytic Bradyrhizobial Cell Differentiation and Its Role in Nitrogen Fixation - Greetatorn, Teerana (Microbes Environ, 2020)
Bradyrhizobium sp. strain SUTN9-2 is a symbiotic and endophytic diazotrophic bacterium found in legume and rice plants and has the potential to promote growth. The present results revealed that SUTN9-2 underwent cell enlargement, increased its DNA content, and efficiently performed nitrogen fixation in response to rice extract. Some factors in rice extract induced the expression of cell cycle and nitrogen fixation genes. According to differentially expressed genes (DEGs) from the transcriptomic analysis, SUTN9-2 was affected by rice extract and the deletion of the bclA gene. The up-regulated DEGs encoding a class of oxidoreductases, which act with oxygen atoms and may have a role in controlling oxygen at an appropriate level for nitrogenase activity, followed by GroESL chaperonins are required for the function of nitrogenase. These results indicate that following its exposure to rice extract, nitrogen fixation by SUTN9-2 is induced by the collective effects of GroESL and oxidoreductases. The expression of the sensitivity to antimicrobial peptides transporter (sapDF) was also up-regulated, resulting in cell differentiation, even when bclA (sapDF) was mutated. This result implies similarities in the production of defensin-like antimicrobial peptides (DEFs) by rice and nodule-specific cysteine-rich (NCR) peptides in legume plants, which affect bacterial cell differentiation.